1995
DOI: 10.1016/0735-1097(95)00156-t
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous revascularization of chronic coronary occlusions: An overview

Abstract: Patients with a chronic coronary occlusion often undergo coronary angiography after weeks to months of occlusion. The published reports underestimate the extent of this problem because such patients are often arbitrarily assigned to receive medical therapy or undergo bypass surgery as a result of poor success with percutaneous revascularization and substantial restenosis. Thus, there is controversy about the role of angioplasty in this patient cohort. The goal of this overview was to evaluate the available inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
137
0
1

Year Published

1997
1997
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(142 citation statements)
references
References 62 publications
4
137
0
1
Order By: Relevance
“…Successful recanalization is achieved in less than 65% of attempted procedures. Inability to cross the lesion with a guidewire is the reason for failure in more than 75% of unsuccessful attempts [1]. To facilitate guidewire crossing, new guidewires have been developed, including a ball-tipped wire [2], the laserwire [3], guidewires with hydrophilic coating [4], and stiff wires with high-torque control (Athlete wire, Asahi Intech, Japan).…”
Section: Introductionmentioning
confidence: 99%
“…Successful recanalization is achieved in less than 65% of attempted procedures. Inability to cross the lesion with a guidewire is the reason for failure in more than 75% of unsuccessful attempts [1]. To facilitate guidewire crossing, new guidewires have been developed, including a ball-tipped wire [2], the laserwire [3], guidewires with hydrophilic coating [4], and stiff wires with high-torque control (Athlete wire, Asahi Intech, Japan).…”
Section: Introductionmentioning
confidence: 99%
“…cohort was reported in 1982 [1], many studies dealing with chronic total occlusions has been reported [2]. The beneficial effects of successful angioplasty for the chronic total occlusion has been reported: Anginal state often improves after successful angioplasty; left ventricular functions may improve [3][4][5]; and subsequent referral for coronary bypass graft surgery is uncommon [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The angioscopic observation showed that fewer incidence of thrombus in the CTO group compared with non-CTO group. Total occlusion comprises athrosclerotic plaque and a single or multiple layers of clot formed by repeat injury repair process [2]. Angioscope can recognize fresh clots as a thrombus, however as the older and more fibrosed clot were present in the lesion with total occlusion, angioscope cannot detect the thrombus.…”
Section: Patients Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The principal challenge of performing angioplasty for a CTO is the safe navigation of a guidewire through the dense collagen blockage without perforating the arterial wall. 2,3 While some experimental imaging guidance technologies have been suggested to differentiate between the blockage and the arterial wall. 4 and hence guide this procedure, these methods are not generally available to interventional cardiologists.…”
Section: Introductionmentioning
confidence: 99%